The Development and Implementation of a Quality Improvement Review Committee (QIRC): An Ethical and Pragmatic Imperative - McMillan, Sarah; Tosoni, Sarah; Smith, Kerry-Ann; Chau, Betty; Oh, Paul; Steele, Catriona; Chartier, Lucas; Heesters, Ann (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2024)
Background: In complex academic healthcare systems, quality improvement (QI) projects designed to improve care and enhance learning proliferate, yet there is considerable variation with respect to how, or even whether, these projects receive ethical oversight. As a result of a high volume of projects that were submitted to one of our research ethics board (REB) panels, but deemed not-research and therefore not eligible for review, questions at our organization began to surface with respect to how the ethical dimensions of QI projects might be assessed, and which institutional approvals might be required to ensure compliance with emerging normative standards. Methods: A mixed-methods environmental scan led to a retrospective quantitative analysis of our organization’s QI projects coupled with in-depth qualitative consultations with staff, physicians, and learners across our health network. REB exemptions were analyzed via run charts to assess baseline QI project volumes and thematic analyses were conducted on field notes from 133 stakeholder consultations. Results: During a 34-month period, 117 REB exemption letters were issued for QI projects. Consultations identified the need for: a clearly defined ethical review process for QI projects, appropriate governance structures, and opportunities to identify and mitigate risk. Respondents also spoke to the ethical imperative to conduct QI initiatives. This paper discusses how these themes contributed to the development and implementation of our Quality Improvement Review Committee (QIRC). Conclusion: Since 2020, over 840 projects have been reviewed by our QIRC, with a view toward mitigating risks for patients, staff, and QI project teams across UHN.